Artistic image memory and its impact on artistic expression - Haider Mahmood, Nawras (Journal of College of Education, 2022)
Abstract Science fiction can allow it to influence the limits that allow you to gradually in the external environment in which you live in the air to possess the information and experiences you are looking for, as the duration of the search varies in the search for the information contained in the search for the information contained in the research. Memory means the process of storing, retrieving and using acquired information and experiences in the future, as the individual relies in most of the daily activities that he performs on retrieving those educational experiences that he acquired as a result of his passing through learning processes in various areas of life, and if any defect occurs in retrieving these experiences, then we find life This individual has an unnatural and imbalanced form. Since memory is a process of storing information and experiences that an individual acquires, so the process of retrieval depends on processing information that means cognitive and skill activities that occur when the information of the stimulus interacts, is organized and stored in one of the levels of memory (direct sensory - short term - long term), as it is related The retrieval process is by the type of information processing, and by the type of processing it means the way in which the excited individual is encoded, and this process differs according to the different contexts that mean the way the tests (measures) are presented to individuals. For the purpose of achieving the objectives of the research, the researcher designed an educational model in the subject of art education and two types of scales, one of which is a verbal memory scale that aims to identify the level of information possessed by the fourth intermediate students in this subject, and the technical pictorial memory scale, which is used as a cognitive achievement test that depends in its components on elements and foundations Technical work, and a skill test that measures (the artistic expression of students) and is measured by the fee analysis form prepared for this purpose.